Local Policing in a Nationalized Police Force: A Study on the Local Teams of The Netherlands' National Police. (28th June 2018) - Terpstra, Jan
Abstract: This article concentrates on the local consequences of the introduction of the Netherlands' National Police. Six local teams of the National Police were studied, using both interviews with officers and observations of police work. Despite the emphasis on standardization, this study showed that there are important differences between these teams. The scale enlargement of the local teams resulted in several negative side effects, such as an increase in driving time of patrol cars in rural areas, and a loss of social bonds between officers in these teams. The aim to replace traditional patrol work by problem-oriented types of policing is hardly realized in practice. Despite the emphasis on the importance of community policing, in fact community officers now have a more isolated position. The introduction of the National Police created more distance between citizens and the police and made that this relationship is now more dependent on abstract forms of communication.